Analysis Of Political Communication Ahead Of The 2024 Presidential Election Case Studies On Political Campaigns, Political Propaganda, Public Opinion, Marketing, Political Advertising, And Political Negotiation - Syamsul Jahidin; Nani Nurani Muksin (Green Publisher Indonesia, 2024)
The 2024 presidential election is an important moment in the political life of a country. This study aims to analyze the role of various aspects of political communsication in the presidential election, including political campaigns, political propaganda, public opinion, political marketing and advertising, and political negotiations. The research methodology uses a holistic approach with quantitative and qualitative data collection through online surveys, interviews, and media content analysis. Key findings highlight the significance of social media in shaping public opinion and the political communication strategies used by candidates. Practical implications of these findings include recommendations for more effective political campaign strategies and the development of more transparent communication policies.